Quality Management and Work Culture on Employee Performance:Mediating Role of Work Loyalty - Sutarman, Asep; Ramdani, Safier; Anjani, Frida K; Pratama, Adam A (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2023)
This study aims to determine and analyze the impact of Quality Management and Work Culture on Employee Performance mediated by the role of Work Loyalty in DKI Jakarta Regional Owned Enterprises (BUMD) in the Property Sector group. The object of research is company employees in the DKI Jakarta Regional Owned Enterprises group in the Property Sector. Respondents who were sampled in this study amounted to 250 samples. The method used in this study is quantitative, using the Structural Equation Modeling (SEM) program with the help of SmartPLS software version 3.29. Quantitative data were obtained from distributing questionnaires by measuring them using a Likert scale to respondents. The results show that work culture is the variable that has the greatest influence on employee performance. This study also found that the second biggest influence that can increase employee performance is the work culture. It is also known that quality management, works culture, and works loyalty simultaneously influence employee performance. The next finding from this study is that works loyalty is an effective mediating variable to bridge the effect of quality management and works culture on employee performance.